Income Diversification, Bank Monitoring, and Risk: Evidence during the COVID-19 Pandemic - Christianti, Ari; Atmaji, Atmaji; Arifin, Taufiq; Risfandy, Tastaftiyan (Asian Academy of Management Journal of Accounting and Finance, 2025)
This article investigates the relationship among income diversification, bank monitoring and financial risk in the context of commercial banks in Indonesia. Using panel data of 91 Indonesian commercial banks operating during the COVID-19 pandemic, we find that income diversification can reduce bank risk, while monitoring is negatively associated with that risk. While our investigation does not indicate that monitoring can alter the impact of income diversification on bank risk, the results suggest that policymakers should adopt banking transformation by diversifying their income, particularly during a crisis such as the COVID-19 pandemic. We also suggest that banks enhance monitoring to obtain a good external perception that can ultimately increase a bank’s stability.